The Example of an Islamic Religious Education Teacher on the Awareness of Muslim Women's Dress in Middle School Students - Amrah, Nurhikmah (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of the research is to analyze the example of Islamic Religious Education Teachers on the Awareness of Muslim Women's Dress in Students at Junior High School Negeri 4 Panca Rijang, Sidrap Regency Methodology: The method used is quantitative with a case study type of research, the research location is at Junior High School Negeri 4 Panca Rijang Sidrap Regency. The instrument used is a questionnaire with descriptive data analysis. Main Findings: Based on the results of descriptive statistical analysis of questionnaire scores related to the variable awareness of Muslim women's clothing of students from 54 respondents, it is known that students who stated that awareness of Muslim women's clothing were in the very poor category were 0 (0%), students who stated that it was bad was 0 (0%) %) people, students who said it was fair were 3 (6%) people, students who said it was good were 32 (59%) people, and students who said their awareness of Muslim women's clothing was in the very good category was 19 (35% ) person. Novelty/Originality of this study: The latest research is trying to examine the awareness of Muslim women's clothing at Junior High School Negeri 4 Panca Rijang, Sidrap Regency.